Prospective Study About the Relationship Between CEUS of Carotid Intraplaque Neovascularization and Ischemic Stroke in TIA Patients - Li, Zhenzhou; Xu, Xianfeng; Ren, Lijie; Shao, Yufeng; Luo, Shuyu; Chen, Shenghua; Guan, Xiaoyun (Frontiers in Pharmacology, 2019)
Objective: To evaluate the relationship between contrast-enhanced ultrasonography (CEUS) of carotid intraplaque neovascularization and ischemic stroke in transient ischemic attack (TIA) patients. Methods: A total of 112 TIA patients were selected for the study. Routine carotid ultrasonic examination was performed for all the patients. CEUS was carried out for consecutive patients with plaque thicker than 2.5 mm in carotid bifurcation and follow-up for at least 24 months. The number of patients with incurrence of ischemic stroke or recurrence of TIA was obtained during the follow-up period. To detect the risk factors for incurrence of ischemic stroke or recurrence of TIA in 24 months, multivariate logistic regression analyses were performed for all the risk factors in all the selected patients. Results: Ninety-one patients underwent CEUS and were followed up at least 24 months. There were statistical differences between recurrent and non-recurrent groups about hypertension, diabetes, hyperlipemia, smoking history, family history of stroke, medication compliance, two-dimensional ultrasound, and CEUS (P < 0.05). The higher CEUS intensity in the carotid plaque was, the higher was the possibility of ischemic stroke or recurrent TIA. Multivariate logistic regression analysis showed that the CEUS characteristics of carotid plaque such as linear enhancement or diffuse enhancement were independent risk factors for ischemic stroke or recurrent TIA in TIA patients (P < 0.05). Conclusion: For carotid plaques, CEUS could evaluate the infusion mode, which could reflect the neovascularization in plaques. CEUS could predict the incurrence of ischemic stroke or recurrence of TIA in TIA patients, which is useful information when making a clinical decision.